Existence of Visum Et Repertum on the Occurrence of Persecution as Evidence of Work Termination - Asri Wijayanti; Achmad Hariri; Agus Supriyo; Basuki Babussalam; Satria Unggul Wicaksana Perkasa (Jurnal Cita Hukum, 2021)
Employment relationships may end due to abuse by workers. The existence of abuse must be medically proven. This research aimed to analyze the existence of a visum et repertum for the occurrence of abuse that can be used as evidence in termination of employment. This legal research was normative with a statutory approach. The results showed that persecution was a criminal act. There was no requirement for a judge's decision in the District Court which already had permanent legal force for the occurrence of persecution as a condition for the validity of the layoff as if the visum et repertum was no longer needed. It was enough that the acts of abuse committed by workers were regulated in the Employment Agreement, Company Regulation or Collective Labor Agreement, then the persecution as a form of an urgent violation can be used as a valid reason for the termination of employment (Article 81 number 37 of the Job Creation Law jo.  Article 151 / 3 Manpower Law jo. article 52/2 Government Regulation 35/2021. The researchers’ efforts to review labor regulations related to urgent violations in the Indonesian manpower system are a form of evaluation of the weaknesses of the Job Creation Law and its implementing regulations can be able to assist legislators to develop and enforce laws that protect certain vulnerable groups namely workers in applying the principle of presumption of innocence.Keywords: Forensics; Persecution; Termination Eksistensi Visum Et Repertum Atas Terjadinya Penganiayaan Sebagai Alat Bukti Pemutusan Hubungan KerjaAbstrakHubungan kerja dapat berakhir karena adanya penganiayaan yang dilakukan oleh pekerja. Adanya penganiayaan harus dibuktikan secara medis. Penelitian ini bertujuan untuk menganalisis adanya visum et repertum atas terjadinya penganiayaan yang dapat digunakan sebagai alat bukti dalam pemutusan hubungan kerja. Penelitian hukum ini bersifat normatif dengan pendekatan perundang-undangan. Hasil penelitian menunjukkan bahwa  penganiayaan adalah perbuatan pidana. Tidak adanya keharusan putusan hakim di Pengadilan Negeri yang sudah memiliki kekuatan hukum tetap atas terjadinya penganiyaan sebagai syarat keabsahan PHK seolah mengakibatkan visum et repertum tidak dibutuhkan lagi. Cukup perbuatan penganiayaan yang dilakukan oleh pekerja diatur dalam Perjanjian Kerja, Peraturan Perusahaan atau Perjanjian Kerja Bersama, maka penganiayaan sebagai wujud telah terjadi pelanggaran yang bersifat mendesak dapat digunakan sebagai alasan keabsahan pemutusan hubungan Kerja (Pasal  81 angka 37 UU Cipta Kerja jo.  Pasal 151 /3 UU Ketenagakerjaan jo.Pasal 52/2 Peraturan Pemerintah 35/2021. Upaya penulis untuk mereview peraturan perburuhan terkait pelanggaran yang bersifat mendesak dalam sistim ketenagakerjaan Indonesia merupakan bentuk evaluasi atas adanyan kelemahan UU Cipta Kerja dan Peraturan pelaksananya, akan dapat membantu legislator untuk mengembangkan dan menegakkan hukum yang melindungi kelompok rentan tertentu yaitu pekerja dalam menerapkan asas praduga tak bersalah.Kata Kunci: Forensik; Penganiayaan; Pemutusan Hubungan Kerja Наличие Visum Et Repertum в случае преследования как доказательство прекращения работы АннотацияТрудовые отношения могут прекратиться из-за жестокого обращения со стороны работников. Наличие жестокого обращения должно быть доказано с медицинской точки зрения. Это исследование было направлено на анализ наличия visum et repertum в случаях злоупотреблений, которые могут использоваться в качестве доказательства при увольнении. Это правовое исследование было нормативным с законодательным подходом. Результаты показали, что преследование было уголовным преступлением. В районном суде не требовалось вынесения решения судьей, которое уже имело постоянную юридическую силу в связи с преследованием в качестве условия действительности увольнения, как если бы в visum et repertum больше не было необходимости. Достаточно того, чтобы акты жестокого обращения, совершенные работниками, регулировались трудовым договором, регламентом компании или коллективным трудовым договором, тогда преследование как форма неотложного нарушения может быть использовано в качестве уважительной причины для увольнения (статья 81 № 37 Закона о создании рабочих мест, ст. 151/3 Закона о рабочей силе, ст. 52/2 Постановление правительства 35/2021. Усилия исследователей по пересмотру трудового законодательства, касающегося неотложных нарушений в индонезийской системе кадровых ресурсов, являются формой оценки Слабые стороны Закона о создании рабочих мест и его подзаконных актов могут помочь законодателям в разработке и обеспечении соблюдения законов, которые защищают определенные уязвимые группы, а именно работников, в применении принципа презумпции невиновности.Ключевые слова: судебная экспертиза; преследование; прекращение действия